2002
DOI: 10.4141/a01-022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of management strategy on growth performance, carcass characteristics, fatty acid composition, and palatability attributes in crossbred steers

Abstract: Effect of management strategy on growth performance, carcass characteristics, fatty acid composition, and palatability attributes in crossbred steers. Can. J. Anim. Sci. 82: 49-57. Crossbred steers (n = 136) were used to evaluate the effect of management strategy on growth performance, carcass characteristics, and fatty acid composition and palatability attributes of beef. Management strategies included: (1) high grain (75% high moisture corn) finishing (HG), or (2) backgrounding with restricted feeding of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…In fact, after complete compensation small or no differences in meat composition were found in calves (Ryan et al, 1993;Laborde et al, 2002). Schoonmaker et al (2001) also found no differences in meat composition derived from weaning management.…”
Section: Carcass and Meat Qualitymentioning
confidence: 61%
“…In fact, after complete compensation small or no differences in meat composition were found in calves (Ryan et al, 1993;Laborde et al, 2002). Schoonmaker et al (2001) also found no differences in meat composition derived from weaning management.…”
Section: Carcass and Meat Qualitymentioning
confidence: 61%
“…The CLA content is variable among tissues and is influenced by diet (Table 4). Pasturing animals has a positive effect on levels of beneficial fatty acids in beef (Laborde et al 2002;Rule et al 2002), while maintaining carcass quality. Grass-fed cattle contained 7.4 mg CLA g -1 lipid in the top round, and those supplemented with 8.5 kg of cracked corn contained 5.1 mg CLA g -1 lipid (Shantha et al 1997; Table 4).…”
Section: Increasing Desirable Fatty Acids In Beef Through Dietary Supmentioning
confidence: 99%
“…Furthermore, α-linolenic (18:3n-3) levels were more than 7 times higher in bison than beef (Table 1). It is well known that diet can alter the fatty acid composition in bison (Rule et al 2002) and beef (Laborde et al 2002;Nuernberg et al 2008). However, changes to diet have less of an effect in a ruminant animal compared to a monogastric, due to bio-hydrogenation of dietary fatty acids in the rumen (Scollan et al 2006).…”
Section: Fatty Acid Compositionmentioning
confidence: 99%